An IL‐12‐Based Nanocytokine Safely Potentiates Anticancer Immunity through Spatiotemporal Control of Inflammation to Eradicate Advanced Cold Tumors. Issue 10 (5th February 2023) - Chen, Pengwen; Yang, Wenqian; Nagaoka, Koji; Huang, George Lo; Miyazaki, Takuya; Hong, Taehun; Li, Shangwei; Igarashi, Kazunori; Takeda, Kazuyoshi; Kakimi, Kazuhiro; Kataoka, Kazunori; Cabral, Horacio
Abstract: Treatment of immunologically cold tumors is a major challenge for immune checkpoint inhibitors (ICIs). Interleukin 12 (IL‐12) can invigorate ICIs against cold tumors by establishing a robust antitumor immunity. However, its toxicity and systemic induction of counteracting immunosuppressive signals have hindered translation. Here, IL‐12 activity is spatiotemporally controlled for safely boosting efficacy without the stimulation of interfering immune responses by generating a nanocytokine that remains inactive at physiological pH, but unleashes its full activity at acidic tumor pH. The IL‐12‐based nanocytokine (Nano‐IL‐12) accumulate and release IL‐12 in tumor tissues, eliciting localized antitumoral inflammation, while preventing systemic immune response, counteractive immune reactions, and adverse toxicities even after repeated intravenous administration. The Nano‐IL‐12‐mediated spatiotemporal control of inflammation prompt superior anticancer efficacy, and synergize with ICIs to profoundly inflame the tumor microenvironment and completely eradicate ICI‐resistant primary and metastatic tumors. The strategy could be a promising approach toward safer and more effective immunotherapies. Abstract : An interleukin 12 (IL‐12)‐based nanocytokine is formulated by a pH‐sensitive polymeric coating strategy. The nanocytokine can spatiotemporally control the inflammation induced by IL‐12, enhancing the antitumoral immunity without initiating systemic response. The nanocytokine can serve as monotherapy and synergize with checkpoint inhibitors to completely eradicate immunosuppressive primary and metastatic tumors without showing side effects.